Efficient photogeneration of nonacene on nanostructured graphene. Issue 9 (24th June 2021) - Ayani, Cosme G.; Pisarra, Michele; Urgel, José I.; Navarro, Juan Jesús; Díaz, Cristina; Hayashi, Hironobu; Yamada, Hiroko; Calleja, Fabian; Miranda, Rodolfo; Fasel, Roman; Martín, Fernando; Vázquez de Parga, Amadeo L.
Abstract : The presence of an unoccupied surface state resonantly coupled to the π* affinity levels of the precursors, spatially localized in the regions where the precursors are adsorbed, produces 100% yield in the photogeneration of nonacenes. Abstract : The on-surface photogeneration of nonacene from α-bisdiketone precursors deposited on nanostructured epitaxial graphene grown on Ru(0001) has been studied by means of low temperature scanning tunneling microscopy and spectroscopy. The presence of an unoccupied surface state, spatially localized in the regions where the precursors are adsorbed, and energetically accessible in the region of the electromagnetic spectrum where n–π* transitions take place, allows for a 100% conversion of the precursors into nonacenes. With the help of state-of-the-art theoretical calculations, we show that such a high yield is due to the effective population of the surface state by the incoming light and the ensuing electron transfer to the unoccupied states of the precursors through an inelastic scattering mechanism. Our findings are the experimental confirmation that surface states can play a prominent role in the surface photochemistry of complex molecular systems, in accordance with early theoretical predictions made on small molecules.